Aktivitas antiproliferasi ekstrak etanol temulawak (Curcuma xanthorrhiza Roxb.) pada sel lestari tumor MCA-B1 dan MCM-B2 secara In Vitro - B.P. Priosoeryanto; R. Sari; L.K. Darusman; R. Tiuria; E.D. Purwakusumah; W. Nurcholis (Hemera Zoa, 2009)
The aim of this research is to observe the antiproliferation activity of temulawak (Curcuma xanthorrhiza Roxb.) ethanol (70%) extract on MCA-B1 and MCM-B2 cell lines in vitro. Cells were cultivated in tissue culture plate 24 wells with vinblastin (positive control) and 5 dose level extracts in 5 replicates. The concentrations of extract were 0 ppm (negative control), 15 ppm (P1), 30 ppm (P2), 45 ppm (P3), 60 ppm (P4), and 75 ppm (P5). After 3 days incubated at 37 derejad C, cells were harvested and total cells were counted using a haemocytometer Neubauer. The results showed that 70% temulawak extract had antiproliferation activity to MCA-B1 and MCM-B2 cell lines. The best result was occured on the 75 ppm doses, with the ant-proliferation activity reached for 70,0% in MCA-B1 cell line and 75.4% in MCM-B2 celll line. Overall, the results indicated that temulawak may have a possible therapeutic potential againts cancer.Keywords: tumor, temulawak, antiproliferation, MCA-B1, MCM-B2, in vitro.